2011
DOI: 10.1143/apex.4.101001
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nonpolar $a$-Plane Nitride-Based Solar Cell on $r$-Plane Sapphire Substrate

Abstract: We fabricated and characterized a nonpolar a-plane nitride-based solar cell on an r-plane sapphire substrate. The maximum external quantum efficiency of the solar cell reached 62% at a wavelength of approximately 400 nm. The open-circuit voltage, the short-circuit current density, and the fill factor of the solar cell were 0.9 V, 4.8 mA/cm2, and 57%, respectively. A conversion efficiency of 1.6% was obtained from the solar cell under a solar simulator of air mass 1.5 G and an irradiation intensity of 155 mW/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Previously, we reported that less strain in the u-GaN template layer can be achieved by replacing a conventional low temperature GaN buffer layer with a sputtered-AlN buffer layer on a c-plane sapphire substrate, where the crystalline quality of both samples was comparable [20]. Since the strain in the epitaxial layer after cooling down is greatly impacted by the strain of an adjacent layer during growth, one can thus infer that the strain and piezoelectric field in the MQWs active region is significantly influenced by the strain of the underlying layer [21][22][23]. In our structure, the epitaxial structure of the green LEDs is identical except for the buffer layer, thus, the strain in the u-GaN template layer can be considered a factor that limits the QCSE in the MQWs.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that less strain in the u-GaN template layer can be achieved by replacing a conventional low temperature GaN buffer layer with a sputtered-AlN buffer layer on a c-plane sapphire substrate, where the crystalline quality of both samples was comparable [20]. Since the strain in the epitaxial layer after cooling down is greatly impacted by the strain of an adjacent layer during growth, one can thus infer that the strain and piezoelectric field in the MQWs active region is significantly influenced by the strain of the underlying layer [21][22][23]. In our structure, the epitaxial structure of the green LEDs is identical except for the buffer layer, thus, the strain in the u-GaN template layer can be considered a factor that limits the QCSE in the MQWs.…”
Section: Resultsmentioning
confidence: 99%
“…2) So far, we have succeeded in fabricating GaInN-based solar cells. [3][4][5][6][7] By improving the crystal quality of GaInN using freestanding c-plane GaN substrates 3) and applying GaInN superlattice (SL) structures, 4) the conversion efficiency has been improved.…”
mentioning
confidence: 99%
“…In the past decade, many relevant research topics like high-In InGaN crystal growth methods on freestanding GaN substrate [34], p-type InGaN doping [35], quantum well designs [36][37][38][39][40], electrode designs [41][42][43][44], concentrator photovoltaics [37,41,45], intermediate band solar cells [46], and reflection-reduced structures [47][48][49] have been studied. Moreover, the nonpolar nitride-based solar cells were investigated on the polarization effect [50,51]. Dahal et al demonstrated a higher than 30%-In InGaN multiple-quantum-well solar cell operation at longer wavelengths (> 420 nm) [38] and illustrated a 3.03% efficiency under increased illumination intensity up to 30 suns [37].…”
Section: Introductionmentioning
confidence: 99%